Designing a FinTech Start-up (MONBOW) in Contemporary Iraq - Ghareeb, Mohammed (2021)
This Master’s thesis aims to develop an applicable business project related to financial service offerings in Iraq. Fintech startups have grown tremendously lately, and they force traditional financial institutions to change their business model in order to survive in the long run. One of the major aspects of a country’s development is related to the financial condition and the level of financial inclusions in the country. Thus, with these new startup concepts, the economic development in Iraq will be more developed and transparent. The first part of this thesis focuses on analyzing the theoretical aspect of financial technology and the financial industry. In addition, the practical part of this Master’s thesis is focusing on a business plan for a startup in Iraq’s market. Several business aspects have been analyzed in this thesis: PESTEL, SOWT, Lean canvas, Marketing plan, Financial plan, Feasibility of the project …etc. Due to the high potential in the market, the business will only suffer loss in the first year of operation using the realistic scenario. From the second year on, the business will achieve a presentable outcome.